Anger and substance use in HIV-positive patients with chronic pain. Issue 2 (1st February 2023) - Yeh, Jih-Cheng; Uebelacker, Lisa A.; Pinkston, Megan M.; Anderson, Bradley J.; Busch, Andrew M.; Abrantes, Ana M.; Baker, Jason V.; Stein, Michael D.
ABSTRACT: Chronic pain increases the risk of substance use in people living with HIV (PLWH). Depression and anxiety have also been identified as risk factors for substance use among PLWH. Relatedly, other negative mood states, such as anger, may influence chronic pain among PLWH. The current cross-sectional study examined whether the distinct negative mood state of anger is associated with substance use among 187 PLWH who report chronic pain. Using negative binomial regression analyses, we found higher levels of anger were positively associated with alcohol use. Higher levels of anger were inversely associated with benzodiazepine use. No association was found between anger and marijuana use, and there were no significant interactions between anger and pain severity on substance use. Our findings suggest that anger is an independent risk factor for substance use among PLWH and chronic pain. Addressing anger may be useful when adapting behavioral therapies in the treatment of pain among PLWH.